2007
DOI: 10.2741/2109
|View full text |Cite
|
Sign up to set email alerts
|

The transport of glutamine into mammalian cells

Abstract: Glutamine has many important functions in mammalian cells, and glutamine transport across cell membranes has accordingly been extensively studied. In the past few years a number of important glutamine transport proteins have been sequenced and their molecular properties have been characterised. In general, four major transporters are important physiologically. These are known as (i) SNAT3 (System N) which is important in glutamine uptake in periportal cells in liver and in across the basolateral membrane of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 39 publications
3
93
0
Order By: Relevance
“…This neonatal peak in GS activity coincides with the period of terminal differentiation and nerve-induced growth of the myotubes (32). Because glutamine transport in skeletal muscle is electrogenic and dependent on innervation (33), the decline in GS activity may well reflect an innervation-dependent increase in the intracellular concentration of glutamine (34), which is known to decrease the halflife of GS protein (4 -6, 35). Cre expression in transgenic MCKCre striated muscle begins just prior to birth and reaches its maximal level only at ϳ10 days after birth (17).…”
Section: Discussionmentioning
confidence: 99%
“…This neonatal peak in GS activity coincides with the period of terminal differentiation and nerve-induced growth of the myotubes (32). Because glutamine transport in skeletal muscle is electrogenic and dependent on innervation (33), the decline in GS activity may well reflect an innervation-dependent increase in the intracellular concentration of glutamine (34), which is known to decrease the halflife of GS protein (4 -6, 35). Cre expression in transgenic MCKCre striated muscle begins just prior to birth and reaches its maximal level only at ϳ10 days after birth (17).…”
Section: Discussionmentioning
confidence: 99%
“…SNAT1 is also responsible for the transport of neutral amino acids into or out of cells in mammals (McGivan and Bungard, 2007). So far, SNAT1 is recognized as a target for oncogene action because the amount of its mRNA is increased in human hepatocarcinoma cells.…”
Section: Gene Expressionmentioning
confidence: 99%
“…For this reason, it must be transported from the extracellular medium into the mitochondria of tumor cells by specific transporters in the plasma and mitochondrial inner membranes. 64 The mitochondrial transport of metabolites is usually one or two orders of magnitude faster than plasma-membrane-related transport. Studies using native vesicles isolated from the mitochondrial inner membrane confirmed the existence of a transport system with a high capacity and specificity for L-glutamine, showing cooperation and strong inhibition of some L-glutamine analogs.…”
Section: Glutamine Metabolismmentioning
confidence: 99%